Perancangan Game Virtual Pet “My Lonely Tofu” - Sacchio Orlando; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
The game "My Lonely Tofu" is a mini-game combined with a Virtual Pet game. This is a PC-based, offline and single player game. In this game, there are 5 mini-games, which are Tofu Quiz, Tap Tofu, Sad Tofu, Tofu Think Alike and Spot Tofu. The goal of this game is to evolve the virtual pet, Lonely Tofu, by taking care of it. Alpha testing is tested by the supervisor while beta testing is tested by 46 respondents. The results of beta testing show that “My Lonely Tofu” is an enjoyable game suitable for all ages, all 5 minigames have different difficulties, the easiest is Tap Tofu and Tofu Quiz is the hardest.